Future Communication, Computing, Control and Management Volume 2 - Zhang, Ying.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
This volume contains revised and extended research articles written by prominent researchers participating in the ICF4C 2011 conference. 2011 International Conference on Future Communication, Computing, Control and Management (ICF4C 2011) has been held on December 16-17, 2011, Phuket, Thailand. Topics covered include intelligent computing, network management, wireless networks, telecommunication, power engineering, control engineering, Signal and Image Processing, Machine Learning, Control Systems and Applications, The book will offer the states of arts of tremendous advances in Computing, Communication, Control, and Management and also serve as an excellent reference work for researchers and graduate students working on Computing, Communication, Control, and Management Research.
From the content: Research on Grid Technology Applied in the China Financial Sector -- Application of Fuzzy C-Means Clustering Based on Principal Component Analysis in Computer Forensics -- Development of a Cross-Platform Remote-Control System Using on Timed Petri Net and SOAP -- A Kind of Mathematic Model of the Porous Gas Diffusion Electrode -- Study of Online Test and Fault Diagnosis Technology Based on ATmega128 -- Reliability Information Fusion based on Bayesian Generalized Mean Operator -- Effect of Lumping Method on Residual Stress Prediction in a Multipass Welded Tee Joint.
Keywords: Engineering; Computer engineering; Microwaves; Telecommunication; Engineering; Communications Engineering, Networks; Microwaves, RF and Optical Engineering; Electrical Engineering